A Modified Syringe Plunger Device Significantly Reduces Guidewire Threading Time Regardless of Experience Level or the Presence of Presbyopia. (June 2019) - Ysa, August; Lobato, Marta; Mikelarena, Ederi; Arruabarrena, Amaia; Gómez, Roberto; de Blas, Mariano; Metcalfe, Matthew; Fonseca, Juan L.
Purpose: To evaluate the efficacy of a new guidewire threading instrument (GTI) in reducing guidewire threading times compared with the traditional freehand method.Materials and Methods: This prospective, controlled, single-center study recruited 100 subjects (mean age 45.2±11.3 years; 43 men) and divided them into 2 groups depending on their professional background: 50 experienced medical personnel (performed or assisted in >50 catheter-based procedures) and 50 medical personnel with no experience in endovascular techniques (inexperienced group). The threading time of both groups was recorded using the conventional freehand method and with the GTI for both 0.035- and 0.014-inch platforms. Users of eyeglasses for presbyopia were tested with and without glasses. Median values are reported with the interquartile range (IQR; Q1, Q3) in parentheses.Results: The mean insertion times with both the 0.035-inch and 0.014-inch guidewires in the overall study group were significantly better with the use of the GTI compared with the traditional freehand method (p<0.001). Both the experienced and the inexperienced participants improved their insertion times using the GTI with both guidewire platforms (p<0.001). The threading time with the new device was also significantly reduced (p<0.001) for both participants with presbyopia and those without. When comparing the median absolute time improvement (difference between freehand/GTI insertion times) for the 0.014-inch platform, the inexperienced group showed a greater improvement in their performance [3.52 seconds (IQR 2.76, 5.12)] compared with the experienced group [1.87 seconds (IQR 1.37, 2.66), p<0.001]. The median "absolute time improvement" was also significantly greater for the presbyopic group [5.75 seconds (IQR 3.14, 8.20)] vs the group without age-related visual impairment [2.64 seconds (IQR 1.65, 3.36), p<0.001].Conclusion: This simple and inexpensive homemade device facilitates wire threading of low-profile catheters and seems to be especially helpful for trainees with no experience and presbyopic operators.